Универсальные математические модели m-пульсных выпрямителей со смешанной RLC-нагрузкой в цепи постоянного тока - Волков, И.В.; Каршенов, Д.П. (Технічна електродинаміка, 2012)
The analytical method is used for derivation of the universal design formula of the m-pulse three phase rectifier. This formula is proposed as mathematical model of an equivalent circuit with current sources of fundamental frequency and current harmonics.